The Basic Concepts Of Islamic Education Management And Its Correlation With Polexsosbud Aspects - Fitriyani , Fitriyani; Kasful Anwar US; As'ad Isma (Cita konsultindo, 2023)
The objects of educational management in this description are all types of management activities that are directly or indirectly involved in educational activities. As the central point of view is educational activities in schools. However, because activities in these schools cannot be separated from formal and non-formal environmental channels, then of course the scope of the education system up to the central level is also discussed. In a classroom environment, the teacher is the administrator. Gutu must carry out management activities. In the school environment, the principal is the administrator. With the understanding that management is management, management, the principal acts as a manager in the school he leads. Apart from administrators at school, there are also education management executors, namely people who work in education offices and training centers or in courses that have roles and duties like administrators at school. The management process involves the main functions of a manager/leader, namely planning, organizing, actuating and controlling. Education management is also a series of joint activities or the entire business control process for cooperation. a group of people in achieving educational goals that have been set in a planned and systematic manner, which are held in a certain environment. Management of education is essentially related to educational goals, people who collaborate, systemic and systematic processes, and the resources that are utilized.